Classic readings on monster theory : demonstrare. - Mittman, Asa Simon, 1976-; Hensel, Marcus (Arc reference., 2018)
This volume gathers a wide range of readings and sources to enable us to see and understand what monsters show us about what it means to be human. This book introduces the most important and influential modern theorists of the monstrous.